ENT in Primary Care : A Concise Guide - Cervoni, Edoardo; Leech, Kim (Springer International Publishing : Imprint: Springer, 2017)
This volume serves as a practical guide for the primary care provider to better understand the clinical history, clinical examination, and accurate management of ENT disease. Additionally, the text aims to help general physicians and nurse practitioners to reduce the number of specialist referrals for patients requiring ENT care. Topics cover the most common ENT symptoms that can expect to be managed in a primary care setting, ENT diagnostic instrumentation for surgery, and how to determine when a patient can be managed in a general practice or referred to secondary care. Other topics cover the history of ENT, common red flags, rhinology, and laryngology. ENT in Primary Care: A Concise Guide will be a useful resource for medical students, general physicians in training, board certified physicians, and nurse practitioners treating ENT patients.
Keywords: Medicine.; Nursing.; Otorhinolaryngology.; elektronické knihy; electronic books